(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The article considers linguisitic means of the influence on the recipient. Attention is paid to the rational and emotional means of influence and persuasiveness of the logical speech is highlighted. The paper argues that the technique ofcontradistinction and opposition assists in the influence on the recipient. According to the author, repetitions highlight and emphasize important points. It is explained that opinion of witnesses of the events, opinion of official people, statistical data are certifying the information and inspires confidence in the information transmitted. The article describes means of emotional means of transmission of information, which helps to enhance the impact on the reader in the press. These includes the use of exclamation and interrogative sentences, inversion, colloquial andevaluativevocabulary, syntactic constructions, parceling, parentheses, etc. The work summarizes, that integrated use of described means creates activity zones in the text, which affects the consciousness and behavior of the reader.